Asymptotics of Eigenfunctions for Sturm-Liouville Problem in Difference Equations - Bas, Erdal; Ozarslan, Ramazan (Amer Inst Physics, 2016)
In this study, Sturm-Liouville problem with variable coefficient, potential function q(n), for difference equation is considered. The representation of solutions is obtained by variation of parameters method for two different initial value problems and trigonometric solutions are found by means of complex characteristic roots. It is proved that these results hold the equation by using summation by parts method. Two estimations of asymptotic expansion of the solutions are established.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 23-29, 2015 -- Rhodes, GREECE
Keywords: Boundary-Conditions; Spectral-Analysis; Eigenvalues